Model Kepemimpinan Perempuan dalam Meningkatkan Profesionalisme Tenaga Pendidik di Sekolah Dasar Islam Ulul Albab Jember - Mohammad Zaini; Riayatul Husnan; Dini Rohmatul Aulia; Saadatu Mukarromatil Arifah (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The professionalism of educators is a crucial factor in improving the quality of education. At Ulul Albab Islamic Elementary School in Jember, some teachers still come from non-educational backgrounds, resulting in less-than-optimal learning processes. This condition requires effective leadership to guide and develop teachers’ potential. Female leadership is particularly interesting to study, as it is often associated with humanistic, communicative, and collaborative approaches in educational management. This study aims to describe the implementation of female leadership models in enhancing teacher professionalism at Ulul Albab Islamic Elementary School Jember, to identify supporting and inhibiting factors, and to illustrate the level of teachers’ professional competence. The research employs a descriptive qualitative approach, using interviews, observations, and documentation as data collection techniques. Data validity was ensured through source triangulation to confirm the accuracy of the findings. The results show that the female principal’s leadership strategy is oriented toward a democratic leadership model, characterized by teacher involvement in decision-making, open two-way communication, and continuous guidance and mentoring. Supporting factors include a strong culture of cooperation, harmonious communication, and the habituation of Islamic activities that foster teachers’ religious character and work ethic. The inhibiting factor lies in the principal’s limited authority due to the complex foundation bureaucracy. Overall, the professionalism of educators has developed well in four key aspects pedagogical, professional, social, and personal through training, formal career development, and professional certification in accordance with national standards.